2005
DOI: 10.1021/bi051137a
|View full text |Cite
|
Sign up to set email alerts
|

The PsbU Subunit of Photosystem II Stabilizes Energy Transfer and Primary Photochemistry in the Phycobilisome−Photosystem II Assembly of Synechocystis sp. PCC 6803

Abstract: The PsbU subunit of photosystem II (PSII) is one of three extrinsic polypeptides associated with stabilizing the oxygen evolving machinery of photosynthesis in cyanobacteria. We investigated the influence of PsbU on excitation energy transfer and primary photochemistry by spectroscopic analysis of a PsbU-less (or deltaPsbU) mutant. The absence of PsbU was found to have multiple effects on the excited state dynamics of the phycobilisome and PSII. DeltaPsbU cells exhibited decreased variable fluorescence when ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 40 publications
5
31
0
1
Order By: Relevance
“…We speculate, however, that the interaction between PBS and PSII, as influenced by Flv2/Flv4, is rather indirect and due to perturbation of the integrity of PSII dimers. Such perturbation also results from mutagenesis of specific subunits of PSII leading to a decrease in energy transfer efficiency from PBS to PSII (Funk et al, 1998;Veerman et al, 2005).…”
Section: Flv2/flv4 Heterodimer and Sll0218 Protein Are Functionally Lmentioning
confidence: 99%
“…We speculate, however, that the interaction between PBS and PSII, as influenced by Flv2/Flv4, is rather indirect and due to perturbation of the integrity of PSII dimers. Such perturbation also results from mutagenesis of specific subunits of PSII leading to a decrease in energy transfer efficiency from PBS to PSII (Funk et al, 1998;Veerman et al, 2005).…”
Section: Flv2/flv4 Heterodimer and Sll0218 Protein Are Functionally Lmentioning
confidence: 99%
“…It has been previously shown that the deletion of the PsbU protein in Synechocystis cells results in the accumulation of excitonically decoupled phycobilisomes, which leads to disruption of energy transfer from phycobilisomes to PSII (Veerman et al, 2005). If similar effect (disconnected phycobilisomes) exists also in Synechococcus then the decreased PSII fluorescence in the PsbU mutant could be explained by the lack of saturation of PSII, which happens when we use the red actinic and measuring flashes.…”
Section: B)mentioning
confidence: 91%
“…The removal of PsbU affects not only the lumenal side and the core but also the stromal side of PSII. It has been reported that removal of PsbU altered primary photochemical processes and led to the accumulation of uncoupled phycobilisomes decreasing the energy transfer from PBs to PSII (Veerman et al, 2005). Recently, flash-induced Chl fluorescence decay and thermoluminescence (TL) measurements performed with a PsbU mutant of Synechococcus PCC 7942 showed that the rate of charge recombination from the S 2 Q A -state is slowed down, as shown by the retarded rate of fluorescence decay and the upshifted peak position of the Q band in the presence of the electron transport inhibitor DCMU (Balint et al, 2006).…”
Section: The Effect Of Psbu At the Donor And Acceptor Side Of Psiimentioning
confidence: 99%
See 2 more Smart Citations